Five years of radiographic evaluation for the peri-implant bone changes of all-on-four implant prostheses constructed from different framework materials using different digital construction techniques - Khloud Ezzat Mourad; Noha Hassan Atwa Hassan Rashed; Gilan Youssef Altonbary; Salah Abdel Fattah Hegazy (BMC, 2024)
Abstract Background There is insufficient evidence recommending a framework material and a CAD/CAM manufacturing technique for mandibular implant-supported prostheses. The study objective was to evaluate the clinical application of different materials and construction techniques used for mandibular All-on-4 prosthesis on circumferential peri-implant bony changes after 5 years. Methods Thirty-six male patients with all-on-4 mandibular implant-supported prostheses were recalled and divided into three groups. Group PK (patients with frameworks milled from PEEK blocks), Group PSM (patients with frameworks milled from soft metal blocks), and Group SLM (patients with frameworks constructed with additive manufacturing; selective laser melting). The circumferential bone level on all implant faces was assessed with a CBCT. Two-way repeated measures ANOVA was used to compare vertical bone loss (VBL) and horizontal bone loss (HBL) between different groups, implant positions, and observation times followed by Tukey's multiple comparisons. Results For all observation times, there was a significant difference in VBL between groups for both anterior and posterior implants (P < .001). For anterior implants, group PSM showed the lowest VBL while group PK showed the highest for anterior and posterior implants. For all groups, HBL significantly increased after 5 years for both anterior and posterior implants (P < .001). For anterior implants, group PSM showed the highest HBL. For posterior implants, group PK and SLM showed the highest. Conclusion Within the study's limitations, mandibular implant-supported fixed frameworks fabricated with either milling from PEEK or soft metal blocks, or additive manufacturing (laser melting technology) exhibited significant vertical and horizontal bone height changes after 5 years. Clinical Trial Registry Number (NCT06071689) (11/10/2023).